Reversal of rivaroxaban anticoagulation by haemostatic agents in rats and primates - Perzborn, Elisabeth; Gruber, András; Tinel, Hanna; Marzec, Ulla M.; Buetehorn, Ulf; Buchmueller, Anja; Heitmeier, Stefan; Laux, Volker (Thrombosis and Haemostasis, 2013)
Rivaroxaban is an oral, direct factor Xa inhibitor for the management of thromboembolic disorders. Despite its short half-life, the ability to reverse rivaroxaban anticoagulation could be beneficial in life-threatening emergencies. The potential of prothrombin complex concentrate (PCC; Beriplex®), activated PCC (aPCC; FEIBA®) or recombinant activated factor VII (rFVIIa; NovoSeven®) to reverse rivaroxaban in rats and baboons was investigated. Anaesthetised rats pre-treated with intravenous rivaroxaban (2 mg/kg) received intravenous rFVIIa (100/400 μg/kg), PCC (25/50 U/kg) or aPCC (50/100 U/kg) after initiation of bleeding. Clotting times and bleeding times (BTs) were recorded. Rivaroxaban was administered as an intravenous 0.6 mg/kg bolus followed by continuous 0.6 mg/kg/hour infusion in baboons. Animals received intravenous aPCC 50 U/kg (2 U/kg/minute) or rFVIIa 210 μg/kg. BT and clotting parameters were measured. In rats pre-treated with high-dose rivaroxaban, PCC 50 U/kg, aPCC 100 U/kg and rFVIIa 400 μg/kg significantly reduced BT vs rivaroxaban alone (5.4 ± 1.4-fold to 1.5 ± 0.4-fold [p<0.05]; 3.0 ± 0.4-fold to 1.4 ± 0.1-fold [p<0.001]; and 3.5 ± 0.7-fold to 1.7 ± 0.2-fold [p<0.01] vs baseline, respectively). In baboons pre-infused with rivaroxaban and then given aPCC, BT increased by 2.0 ± 0.2-fold and aPCC returned BT to baseline for the duration of its infusion. rFVIIa reduced BT from 2.5 ± 0.3-fold over baseline to 1.7 ± 0.3-fold over baseline. Prolongation of prothrombin time was reduced by PCC, aPCC and rFVIIa in both species. Rivaroxaban reduced thrombin-antithrombin levels; application of PCC and aPCC, but not rFVIIa, increased these levels. In conclusion, PCC, aPCC or rFVIIa have the potential to reverse the anticoagulant and anti-haemostatic effects of rivaroxaban.
Keywords: Baboons; prothrombin complex concentrate; rats; recombinant factor VIIa; rivaroxaban